Menara Majlis Perbandaran Seberang Perai, Pulau Pinang / Nur Adha Radhiah Ab Llah ... [et al.] - Ab Llah, Nur Adha Radhiah; Baharuddin, Nur Asma’ul-Husna; A.Rahman, Nur Anis; Azemi, Nur Amanina; Mat Ropi, Mohd Safiq Aizat; Che Anuar, Muhamad Azmi; Mat Zin, Muhamad Afiq Azfar (2013)
Majlis Perbandaran Seberang Perai (MPSP) or Municipal Council of Province Wellesley is a local authority which administers of Seberang Perai. MPSP are under Penang state government. MPSP are responsible for public health and sanitation, town planning, environment protection and building control for the Seberang Perai building, social and economic development and general maintenance for urban infrastructure. The MPSP headquarters are located at Bukit Mertajam. Starting MPSP are Seberang Perai or known as Province Wellesley was a British colony in 1800 and administration was located in Penang. With the area of 489.3 sq. km, it was populated by only five thousand people but this swampy jungle was progressively development into agriculture land starting from pioneering exploration in 1850. After the signing of the Pangkor Agreement in 1874, the area of Province Wellesley as increased to 740.12 sq. km. Population had be increased due to the opening of the new township of Butterworth and Bukit Mertajam. However, the area coverage of Seberang Perai currently stands at 738.41 sq. km. the reduction in area is due to changes in the alignment of Sungai Muda (Muda River) which demarcates the border between Kedah and Penang. In 1896, the Municipal Ordinance was introduced to enable the State Government to make Rules for the conduct of public affairs. In 1913, a new ordinance has been issued which has empowered the State Government establish the Rural Development Board. Town Council Butterworth and Bukit Mertajam and the Council of the Rural North, Central and South were formed. These three Rural Authorities were merged to become the District Authority in 1961. On 1st July 1974, under the local government law, the three authorities were combined to from the Board OF Administration of Seberang Perai Local Government. Finally, under the Local Government Act 1976, history was created on 15th December 1976 when the Board was succeeded by and recognized as the Municipal Council as the Municipal Council of Seberang Perai or MPSP, the largest local authority in Malaysia.